2017
DOI: 10.1038/cddis.2017.563
|View full text |Cite
|
Sign up to set email alerts
|

A new molecular mechanism underlying the EGCG-mediated autophagic modulation of AFP in HepG2 cells

Abstract: Epigallocatechingallate (EGCG) is a major bioactive component of green tea and is associated with health benefits against multiple diseases including cancer. As an indicator of hepatocellular carcinoma (HCC), high levels of α-fetal protein (AFP) are related to malignant differentiation and poor prognosis of cancer cells. In this study, EGCG can effectively reduce AFP secretion and simultaneously induce AFP aggregation in human HCC HepG2 cells. EGCG-stimulated autophagy induces the degradation of AFP aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…LC3 proteins have not been thoroughly explored by systematic biomolecular simulations or other computational structural methods. Among the simulations present in the literature, each one focused on specific aspects of LC3B dynamics using all-atom molecular dynamics (MD) simulations with a single force field (Jatana et al, 2019;Liu et al, 2013;Nuta et al, 2018;L. Zhao et al, 2017) or coarse-grained approaches (Thukral et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…LC3 proteins have not been thoroughly explored by systematic biomolecular simulations or other computational structural methods. Among the simulations present in the literature, each one focused on specific aspects of LC3B dynamics using all-atom molecular dynamics (MD) simulations with a single force field (Jatana et al, 2019;Liu et al, 2013;Nuta et al, 2018;L. Zhao et al, 2017) or coarse-grained approaches (Thukral et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…EGCG has always achieved a milestone in the quest for cancer therapy. It has been observed to suppress breast cancer [5][6][7], prostate cancer [8][9][10], lung cancer [11][12][13], pancreatic cancer [14][15][16], and liver cancer [17,18]. All of this anticancer activity by EGCG has previously been demonstrated that EGCG is the most effective cancer chemopreventive polyphenol in green tea [19].…”
Section: Introductionmentioning
confidence: 88%
“…Western blot analysis. Protein extraction and western blot analyses were performed as previously described (26) Following 72 h of cell transfection with lentivirus, cells were seeded in 96-well plates at 5,000 cells/well. At the time of detection, 10 µl CCK-8 solution was added to each well, and the absorbance was measured at 450 nm using a microplate reader (Thermo Fisher Scientific, Inc.) after 90 min.…”
Section: Methodsmentioning
confidence: 99%